Pop the balloon: rapid switch from Intra‐aortic balloon pump to alternate device. Issue 8 (10th August 2021) - Long, Ashleigh; Stelling, Kelly; Baran, David A.
Abstract: When a patient with an intra‐aortic balloon pump needs different support, it is simple to use a stiff 0.018‐inch interventional wire (360 cm) to exchange the balloon for a new sheath. This allows the team to start with a balloon and then switch if the support is not sufficient. Abstract : When a patient with an intra‐aortic balloon pump needs different support, it is simple to use a stiff 0.018‐inch interventional wire (360 cm) to exchange the balloon for a new sheath. This allows the team to start with a balloon and then switch if the support is not sufficient.